Real Time Tool Wear Condition Monitoring in Hard Turning of Inconel 718 Using Sensor Fusion System. (2017) - Mali, Rahul; Telsang, M.T.; Gupta, T.V.K.
Abstract: The work presented here is an attempt to introduce a sensor based tool wear monitoring system for hard turning of Inconel718 material. Tool wear is a significant factor which influences surface finish, production time and economy of tooling. Hence, an online tool wear monitoring system has been developed using a sensor fusion system, consisting of a vibration sensor and a force based measurement system. Nine experimental runs based on L9 orthogonal array of Taguchi method are performed and analysis of variance (ANOVA) is carried out to identify the significant parameters. The second part of the study include extended period turning operation performed till the tool is worn out completely. Both vibration and force signals are captured by a data acquisition system. The study shows that force data is quite useful to establish a strong correlation between the cutting force and tool wear. Cutting forces establishes a uniform correlation with tool wear which can effectively be used for online tool wear measurement. The effectiveness of these signals to predict tool wear has been established with a MATLAB based GUI that directly displays the real time tool wear.